Evaluating Pedagogical Strategies for Pedestrian Safety Education Among High School Students - Aninwaa, Matilda; Fosu, Gabriel Obed; Lawer, Emmanuel; Sakyi-Yeboah, Emmanuel (Journal of Pedagogy and Education Science, 2025)
Pedestrian-related accidents are a significant public health concern, particularly in sub-Saharan Africa, where pedestrian fatalities among young people continue to rise. In Ghana, the absence of targeted pedestrian safety education in senior high schools contributes to these fatalities. This study aims to assess the knowledge of pedestrian safety among senior high school students and evaluate their preferred learning strategies for safety education. Using a descriptive survey design, data were collected from 103 students in the Ashanti Region of Ghana. Quantitative methods, including descriptive statistics and regression analysis, were employed to analyze the data. The results revealed that while 75.7% of students demonstrated adequate knowledge of pedestrian signs, only 35% had sufficient knowledge of pedestrian safety rules. Students expressed a clear preference for active learning strategies, with outdoor practical exercises and roleplay rated as the most effective methods. No significant relationship was found between students’ gender and the effectiveness of these strategies, suggesting that interactive teaching methods are universally effective across demographic groups. The findings highlight the need to integrate student-centered, experiential learning methods into the national curriculum to enhance pedestrian safety education.